The Dilemma of Humanitarian Intervention: Evaluating the Causes and Consequences of the International Intervention in Libya since 2011 - Mahmoud, Reem (AUC Knowledge Fountain, 2018)
“At this time of extreme challenges, we must not abandon the responsibility to protect or leave it in a state of suspended animation, finely articulated in words but breached time and again in practice.” António Guterres 2018. Since the 1990s, the international community has utilized a growing range of measures to protect populations from mass atrocities, war crimes, genocides and crimes against humanity; however, the numbers of victims, casualties and human losses are increasing daily all over the world. The international community is still unable to protect civilians most in need and those under real threat, even while applying the principle of the humanitarian intervention. The international response to the crisis in Libya during its popular uprising in 2011 was remarkably quick and decisive; the UNSC endorsed for the first time in history a resolution (1973) to authorize the international intervention in another state, to protect civilians under threat, without the approval of its government; in this regards, the adoption of such resolution was declared a turning point in the history of the principle of the Responsibility to Protect. The principle of humanitarian intervention has always been a debatable issue; while most studies focus on the dilemma of its legality, ethics, morality, types and intervening actors, this research focuses on evaluating its outcome and analyzing the factors contributed to its success/failure, while having Libya as a case study. After the intervention in Libya, the country has been characterized by state collapse, anarchy and chaos, and the intervention was considered a failure to the international community and to the principle of the responsibility to protect. In this regards, this research argues that the intervention of the international community in Libya was responsible for the intensification of the sufferings, deterioration and threats facing the civilians in Libya post the intervention stage. While clarifying that the abuse of the international intervention and the fragility of the Libyan state are the main factors behind the collapse of Libya. In addition, this research draws lessons for the future of the principle.